Proceedings of the Third Central European Cybersecurity Conference 2019
DOI: 10.1145/3360664.3362698
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Threat Modeling and Automated Test Case Generation into Industrialized Software Security Testing

Abstract: Industrial Internet of Things (IIoT) application provide a whole new set of possibilities to drive efficiency of industrial production forward. However, with the higher degree of integration among systems, comes a plethora of new threats to the latter, as they are not yet designed to be broadly reachable and interoperable. To mitigate these vast amount of new threats, systematic and automated test methods are necessary. This comprehensiveness can be achieved by thorough threat modeling. In order to automate se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…However, similar to the previous case, automation is only applied to the security testing and not to the model creation (Marback et al 2013). In Marksteiner et al (2019), a method to use threat models was demonstrated to automate security tests towards Industrial Internet of Things devices. In Patil and Pawar (2012), web applications were targeted, future possibilities were discussed, and several problems were identified that must be solved to achieve automated model creation for fully automated testing.…”
Section: Automated Threat Modelingmentioning
confidence: 99%
“…However, similar to the previous case, automation is only applied to the security testing and not to the model creation (Marback et al 2013). In Marksteiner et al (2019), a method to use threat models was demonstrated to automate security tests towards Industrial Internet of Things devices. In Patil and Pawar (2012), web applications were targeted, future possibilities were discussed, and several problems were identified that must be solved to achieve automated model creation for fully automated testing.…”
Section: Automated Threat Modelingmentioning
confidence: 99%